The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1242/jcs.196147
|View full text |Cite
|
Sign up to set email alerts
|

Loss of β-PIX inhibits focal adhesion disassembly and promotes keratinocyte motility via myosin light chain activation

Abstract: During healing of the skin, the cytoskeleton of keratinocytes and their matrix adhesions, including focal adhesions (FAs), undergo reorganization. These changes are coordinated by small GTPases and their regulators, including the guanine nucleotide exchange factor β-PIX (also known as ARHGEF7). In fibroblasts, β-PIX activates small GTPases, thereby enhancing migration. In keratinocytes in vitro, β-PIX localizes to FAs. To study β-PIX functions, we generated β-PIX knockdown keratinocytes. During wound closure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…We used the FLP/FRT system to generate clones of dpix or git mutant tissue in otherwise heterozygous animals, and found that loss of dpix or git causes multilayering of the follicular epithelium (Fig 1H–1I’), even in small clones (S1G Fig), indicating that the requirement for dpix and git is autonomous to the follicle cells. Interestingly, while PIX and GIT proteins are known to influence focal adhesion turnover and maturation in cell culture systems [3841], we did not see an obvious effect on the accumulation of the focal adhesion component talin in monolayered dpix or git mutant tissue (Fig 1H–1I’), however talin levels were often increased in multilayered tissue (S1E and S1F Fig). We did not see a general disruption of apical-basal polarity in monolayered clones, as indicated by unchanged apical localisation of β-heavy-spectrin in dpix clones (S1H–S1H’ Fig).…”
Section: Resultsmentioning
confidence: 64%
“…We used the FLP/FRT system to generate clones of dpix or git mutant tissue in otherwise heterozygous animals, and found that loss of dpix or git causes multilayering of the follicular epithelium (Fig 1H–1I’), even in small clones (S1G Fig), indicating that the requirement for dpix and git is autonomous to the follicle cells. Interestingly, while PIX and GIT proteins are known to influence focal adhesion turnover and maturation in cell culture systems [3841], we did not see an obvious effect on the accumulation of the focal adhesion component talin in monolayered dpix or git mutant tissue (Fig 1H–1I’), however talin levels were often increased in multilayered tissue (S1E and S1F Fig). We did not see a general disruption of apical-basal polarity in monolayered clones, as indicated by unchanged apical localisation of β-heavy-spectrin in dpix clones (S1H–S1H’ Fig).…”
Section: Resultsmentioning
confidence: 64%
“…β-PIX also accumulates in assembling nascent adhesions in the absence of NMII contractility, and it dissociates from focal adhesions during NMII-meditated focal adhesion maturation ( Kuo et al , 2011 ). In fibroblasts, astrocytes, and certain epithelial cells, β-PIX is a negative regulator of focal adhesion maturation ( Zhao et al , 2000 ; Kuo et al , 2011 ), and loss of β-PIX inhibits focal adhesion disassembly ( Kuo et al , 2011 ; Hiroyasu et al , 2017 ). Indeed, cells depleted for Scrib exhibit large continuous focal adhesions, and we propose that β-PIX in these cells is inactive, leading to aberrant focal adhesion dynamics because of the inhibition of focal adhesion disassembly.…”
Section: Discussionmentioning
confidence: 99%
“…A key role for βPIX in the regulation of adhesion dynamics and cell migration has also been shown to support lamellipodial protrusions by negatively regulating adhesion maturation and promoting rapid adhesion disassembly 32 . In keratinocytes, βPIX is localized to adhesions in the leading edge during single cell migration and is important for recruiting PAK to adhesions 33 .…”
Section: Introductionmentioning
confidence: 99%